2017
DOI: 10.2152/jmi.64.24
|View full text |Cite
|
Sign up to set email alerts
|

The Posterior Condylar Cartilage Affects Rotational Alignment of the Femoral Component in Varus Knee Osteoarthritis

Abstract: : Rotational alignment of the femoral component in total knee arthroplasty (TKA) is important for patellar tracking and ligament balance. Preoperative planning based on radiography might have a potential risk for over-rotation because these X-ray based measurements can not detect asymmetric cartilage wear on posterior condyle. The purpose of this study is to evaluate the effect of the posterior condylar cartilage of varus osteoarthritic knee on rotational alignment of the femoral component in TKA. We establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
(18 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, anatomical variability among patients, especially the degree of osteoarthritis, may impede correct measurement [ 17 ]. It is difficult to match the TEA observed on the radiograph with that seen intraoperatively [ 12 ]. For this reason, the PCA is used as a reference to find the TEA axis in the surgery using mechanical alignment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, anatomical variability among patients, especially the degree of osteoarthritis, may impede correct measurement [ 17 ]. It is difficult to match the TEA observed on the radiograph with that seen intraoperatively [ 12 ]. For this reason, the PCA is used as a reference to find the TEA axis in the surgery using mechanical alignment.…”
Section: Discussionmentioning
confidence: 99%
“…In most osteoarthritic knees, the medial and lateral cartilages of the posterior condyle have different thicknesses because of asymmetric cartilage wear [ 10 ]. Previous studies using MRI have shown that posterior cartilage loss alters the apparent femoral condylar twist angle [ 11 , 12 ]. These studies have proved that the angle of the TEA relative to the PCA is significantly greater in the presence of cartilage than in the absence of cartilage [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…More external rotation of the femoral component with the measured resection technique can be attributed to cartilage wear of the medial condyle which has been reported by several researchers. 13,28 In the measured resection technique, the femoral component generally is placed in a condition of 3 or 5 degrees external rotation against the PCA using an instrument made by the implant manufacturer. However, Hamada et al 28 argued that wear of the medial cartilage can affect rotational alignment of the femoral component.…”
Section: Discussionmentioning
confidence: 99%
“…13,28 In the measured resection technique, the femoral component generally is placed in a condition of 3 or 5 degrees external rotation against the PCA using an instrument made by the implant manufacturer. However, Hamada et al 28 argued that wear of the medial cartilage can affect rotational alignment of the femoral component. They reported that the femoral component could be externally rotated more than the original target because of cartilage wear.…”
Section: Discussionmentioning
confidence: 99%